Effect of Nano-Hydroxyapatite Incorporation into Resin Modified Glass Ionomer Cement on Ceramic Bracket Debonding - Mohsen Nuri Sari; Elahe Seyed Tabaii; Abbas Salehi Vaziri; Hasanali Ghaffari; Mehdi Araghbidi Kashani; Gholamreza Eslami Amirabadi (Islamic Dental Association of Iran, 2014)
Background and Aim : Preventing enamel demineralization around brackets is a concern for orthodontists. Fluoride releasing materials have been recommended to overcome this problem. The aim of this study was to evaluate the effect of incorporating nano-hydroxyapatite (NHA) into resin modified glass ionomer cements (RMGIC) on ceramic bracket debonding .   Materials and Methods : In this experimental study, 80 human premolars were divided into 4 bonding groups as follows: group 1: Transbond XT (control group), group 2: Fuji II LC (RMGIC), group 3: 5% NHA added to RMGIC and group 4 10% NHA added to RMGIC. After enamel etching, ceramic brackets were bonded. The shear bond strength (SBS) and the adhesive remnant index (ARI) were calculated for each group. The data were analyzed using one-way ANOVA, Tukey's post hoc HSD test and the Kruskal Wallis test .   Results : According to ANOVA, 10% NHA added to RMGIC had a significantly lower SBS compared to other groups (11.93±2.11) but no significant difference was found among the remaining groups. The mean SBS was 17.33±4.07 in group 1, 17.22±3.55 in group 2 and 16.56±2.59 in group 3. According to ARI, the predominant failure mode in RMGIC groups was cohesive .   Conclusion: Resin modified glass ionomer cements containing 5% NHA can be as effective as composite resins for bonding ceramic brackets .